2022
DOI: 10.3390/plants11131773
|View full text |Cite
|
Sign up to set email alerts
|

An Interplay of Light and Smoke Compounds in Photoblastic Seeds

Abstract: Light increases the germinability of positively photoblastic seeds and inhibits the germination of negative ones. In an area where plant-generated smoke from fire is a periodically occurring environmental factor, smoke chemicals can affect the germination of seeds, including those that are photoblastically sensitive. Moreover, as smoke and its compounds, mostly karrikin 1, KAR1, have been used for priming the seeds of many species, including photoblastic ones, a systematic review of papers dealing with the phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
3
0
1
Order By: Relevance
“…Therefore, not only the smoke-specific molecules but also environmental factors characteristic of the local environment must be considered. The active concentration of KAR differs in different species [54].…”
Section: Common Physiological Mechanisms Of Smoke Compounds On Plant ...mentioning
confidence: 99%
“…Therefore, not only the smoke-specific molecules but also environmental factors characteristic of the local environment must be considered. The active concentration of KAR differs in different species [54].…”
Section: Common Physiological Mechanisms Of Smoke Compounds On Plant ...mentioning
confidence: 99%
“…In positively photoblastic seeds, germination is promoted by white light, whereas in negatively phoblastic seeds, germination is inhibited [17]. It has been shown that chemicals from plantgenerated smoke (e.g., karrikins) can affect the germination of photoblastically sensitive seeds [50]. Seeds of many weeds require exposure to light for germination.…”
Section: Seed Germination: the Initiation Of A New Generationmentioning
confidence: 99%
“…Therefore, not only must the smokespecific molecules be considered, but so must environmental factors characteristic of the local environment. It must be emphasized that the active concentration of KAR differs in smoke produced through the combustion of different plant species [58].…”
Section: The Impact Of Smoke and Its Isolated Compounds On Seed Germi...mentioning
confidence: 99%